Intelligent Wireless Ultrasonic Device for Damage Detection of Metallic Structures - Shrestha, Manish Man; Ropakheti, Bibek; Bhattarai, Uddhav; Adhikari, Ajay; Thakur, Shreeram (Scientific World, 2021)
In today’s world, it is necessary to monitor structures for possible damages. A failure to monitor the structures properly can cause structural catastrophe. Many researchers have worked on the low-power ultrasonic device to monitor the structures. In this research, we present an intelligent ultrasonic device (IUD) to monitor and detect the damages on the structures. The device uses microcontroller, actuator interface circuit, sensor interface circuit and radio frequency (RF) modem. The microcontroller has in-built high-speed analog-to-digital converter (ADC), digital-to-analog converter (DAC) and floating-point unit for signal processing. The controller generates the tone-burst signal and sends it to actuator interface circuit. The actuator interface circuit conditions the received signal from the microcontroller and drives the Piezoelectric Transducer (PZT) actuator. The actuator generates an ultrasonic wave in the structure. The wave is then sensed by PZT sensors. The sensor interface circuit selects the signal from desired PZT sensor and sends it to the microcontroller for further processing. The microcontroller digitizes the signal and computes the damage index and only if the damage is severe, it will send data wirelessly to the nearby PC. To test the device, iron specimen was prepared, PZT actuator and PZT sensor was mounted on it. The artificial crack was then induced on the specimen. The ultrasonic wave was then collected from the structure. By analyzing the ultrasonic wave, the device successfully detected the induced crack in the structure. The future work will be to use GSM modem so that the device can be monitored in the real time from the remote location.